Mainstream Ideological Education Discourse of Post-00s College Students in the Era of Omnimedia the Logic of the Improvement of Guidance Force - Zeng, Ying (International Journal of Humanities and Social Science, 2026)
The all-media revolution has fundamentally reshaped the cognitive landscape of Generation Z college students, exposing mainstream ideological education to three critical challenges: erosion of discourse authority, narrative disengagement, and entrenched cognitive barriers. This study examines three key dimensions-societal ideological infiltration, algorithmic technology distortion, and lagging media literacy-to reveal the deep-seated causes of mainstream discourse’s declining influence. It proposes a three-pronged optimization strategy: establishing an "agenda-setting and discourse absorption" mechanism to strengthen mainstream discourse definition; employing algorithmic recommendations for precision-targeted outreach to break information cocoons; and implementing media literacy programs to solidify the foundation of critical thinking.